1986
DOI: 10.1177/004051758605600909
|View full text |Cite
|
Sign up to set email alerts
|

Skin Friction and Fabric Sensations in Neutral and Warm Environments

Abstract: The influence of skin friction on the perception of fabric texture and pleasantness (acceptability) was studied by exposing eight men to a sequence of environmental conditions: neutral (comfortable), hot-dry, hot-humid, and return to neutral. The air and dew point temperatutes ( T a : T dp ) of these conditions were 23:15°C, 35:15°C, 35 :29°C, and 23:15°C, respectively; air velocity was 0.05 m/s. During each condition, which lasted 20 minutes, six different fabrics (worsted wool, brushed cotton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
102
1
12

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(122 citation statements)
references
References 11 publications
(25 reference statements)
5
102
1
12
Order By: Relevance
“…There were some evidences that thermal sensation and clothing sensation are associated with skin wetness [10,11]. The more widely moisture is distributed over the skin, the stronger the discomfort sensation [12,13]. In the present study, the participants reported higher thermal sensation, greater thermal discomfort, and more wetness sensation when wearing the tight-fit than the loose-fit clothing.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…There were some evidences that thermal sensation and clothing sensation are associated with skin wetness [10,11]. The more widely moisture is distributed over the skin, the stronger the discomfort sensation [12,13]. In the present study, the participants reported higher thermal sensation, greater thermal discomfort, and more wetness sensation when wearing the tight-fit than the loose-fit clothing.…”
Section: Discussionsupporting
confidence: 48%
“…In the present study, the participants reported higher thermal sensation, greater thermal discomfort, and more wetness sensation when wearing the tight-fit than the loose-fit clothing. A study suggested that increase contact of the skin with the clothing in tight-fit clothing increase dampness and lead to negative impact of thermal comfort [12]. In addition, more sensation of skin wetness would affect the weight of the garment, impair heat dissipation from the skin, and post-exercise impairment evaporative cooling [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…The kind of clothing and the material it is made of may determine the overall comfort of an individual wearing it [1][2][3][4] and have impact on his/her everyday activities. The clothing material may also have influence on the results achieved in professional athletics, as well as on the efficiency in non-sportive activities.…”
Section: Introductionmentioning
confidence: 99%
“…Svaka senzacija izazvana specifičnim fizičkim impulsom doprinosi sveobuhvatnoj percepciji komfora (slika 16) [186]. Brojna istraživanja potvrdila su izuzetnu složenost prisutnih relacija između vlakana, pređa i tekstilnih materijala kao i njihov uticaj na čulni aspekt komfora [58,154,155,187,188].Slika 16. Čulni aspekt komfora odeće Tokom nošenja odeće ostvaruje se neposredan, dinamičan kontakt odeće i kože na gotovo čitavoj površini čovekovog tela.…”
unclassified
“…Nervni završeci, receptori bola, vrlo su blizu površine maljave kože za razliku od glatkih regiona kože (prsti) pa oni ne mogu da registruju peckanje. Sa povećanjem sadržaja vlage na koži raste osećaj peckanja jer voda omekšava mrtvi sloj ćelija na koži tako da štrčeća vlakna lakše prodiru.Osetljivost na peckanje raste i sa povećanjem temperature okruženja u intervalu 12 -32 °C, jer usled pojačanog znojenja raste sadržaj vlage na koži [188]. Svrab predstavlja senzaciju koja je rezultat aktiviranja izvesnih površinskih receptora bola, koji se mogu razlikovati od receptora odgovornih za senzacije peckanja [52].…”
unclassified